The relationship between sexual health and personality type in women with epilepsy - Alieh Sheikhalishahi; Fereshteh Jahdi; Hamid Haghani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Sexual health in the development of the human personality, personal, and social health and in achieving to comfort plays an important role. Women with epilepsy are at high risk of sexual dysfunction, which has a multifactorial etiology. This study is aimed to investigate the correlation between the sexual function of women with epilepsy and personality factors. MATERIALS AND METHODS: this cross-sectional study was conducted on 100 women with epilepsy referred to selected centers in Tehran university of medical sciences by using continuous and availability sampling method between January and March 2014 (Iran) and evaluated with women's sexual function index questionnaire female sexual function index and NEO-five-factor of personality inventory. Data were analyzed using SPSS software version 16 and Pearson correlation test. RESULTS: The mean sexual function overall score in participations was 23.33 ± 2.82 there was a significant negative correlation between neuroticism and sexual function (P = 0.00, r = −0.03) and was significant positive correlation between personality traits as extraversion (P = 0.00, r = 0.63), agreeableness (P = 0.008, r = 0.26) and conscientiousness (P = 0.04, r = 0.20) and openness to new experiences (P = 0.03, r = 0.21) and sexual function in women with epilepsy. CONCLUSIONS: Results indicate that the personality traits can affect on sexual health and sexual function of women with epilepsy. Therefore, it is recommended that health-care providers with assess personality factors in women with epilepsy as a prognostic factor, take steps to prevent sexual dysfunction.